Interfacial bonding properties between cobalt-based plasma cladding layer and substrate under tensile conditions. (5th June 2017) - Li, Yang; Cui, Xiufang; Jin, Guo; Cai, Zhaobing; Tan, Na; Lu, Bingwen; Gao, Zonghong
Abstract: Bonding strength is critical to the service life of components in the surface engineering field. To identify the interfacial bonding behavior of metallurgical coating and substrate, micro-plasma cladding technique was used to fabricate cobalt-based metallurgical coating, meanwhile niobium and cerium oxide as reinforced particles were added to the composite coating. The elastic modulus of coating and substrate were measured to assess the matching degree of elastic coefficient between coating and substrate. In addition, the bonding properties of coating and substrate were tested. Result, the microstructure was refined by the addition of niobium and cerium oxide. The composite coating mainly consisted of γ-Co, Cr23 C6, M7 C3, Ni2 Si and NbC. Interface is face-centered cubic structure and the main elements are iron and cobalt near the interface. Tensile and elastic modulus tests demonstrate an excellent match between the coating and substrate. With the addition of niobium and cerium oxide alone or in combination, the tensile performance was improved significantly. The bonding strength of the coating and substrate is superior to that of the coating itself. The fracture occurred in the interface between the two coatings instead of interior of single plasma cladding layer. Graphical abstract: Highlights: Metallurgical interface is face-centered cubic structure and the main elements are iron and cobalt near the interface. Bonding properties were tested by tensile test with the aid of a special fixture. The bonding strength between coating and substrate was stronger than that of the coating itself.